Replication data for: Enchaînement, liaison, accentuation chez les apprenants norvégiens - Andreassen, Helene N.; Lyche, Chantal (DataverseNO, 2015)
[abstract] Given that their L1, Norwegian, and their L2, English, are lexical stress languages, Norwegian speakers will equally tend to stress lexical words during the course of acquisition of L3 French, insuring the prosodic autonomy of each word. In the present paper, we show that this strategy slows down the acquisition of two external sandhi phenomena in French, i.e. liaison and final consonant linking. The data, taken from two corpora recently collected in Tromsø and Oslo, indicate that the learners' acquisition path is conditioned by internal factors like prosodic weight, perceptual salience and frequency, and by external factors like the different tasks to be completed, i.e. reading vs conversation. The data further indicate that liaisons following determiners and clitics are the first categories to be acquired and that spontaneous speech, where the learner does not have direct access to the graphic word, seems to favor erasing the prosodic boundaries required by the prosodic system of her L1. The dataset is based on data from 12 Norwegian learners, 6 from Tromsø (level A2) and 6 from Oslo (level B1/B2), participants in the ongoing project IPFC: Interphonologie du français contemporain (http://cblle.tufs.ac.jp/ ipfc/index.php?id=2). Data are extracted from three registers: text reading, semi-formal conversation and free conversation. The dataset consists of four Excel-files, plus a read-me file. The files "Enchainement_text" and "Enchainement_conversation" contain all potential occurrences of enchainement (rightward consonant linking across a word boundary) observed in the three registers, as well as (non) enchainement of the consonant in the various cases. The files "Liaison_text" and "Liaison_conversation" contain all potential occurrences of liaison observed in the three registers. It further contains information on (non) liaison and (non) enchainement in the various cases, as well as, when a liaison consonant is realised, the type and quality of the consonant produced.